The Prevalence of Anosmia and Dysgeusia in Relation to Sex, Age, and Smoking during COVID-19 Second Wave: A Retrospective Analysis of a Sample of Patients in Hilla City - Maytham Riad Ali; Malath Azeez Al-Saadi (Medical Journal of Babylon, 2024)
Background: Olfactory and gustatory dysfunction are among the significant symptoms of COVID-19 infection that show diversity in prevalence and recovery with a great impact on patients’ life. Objectives: This study aimed to evaluate the impact of age, sex, and smoking on the prevalence and recovery of dysgeusia (abnormal taste) and anosmia (loss of smell) in COVID-19-infected patients. Materials and Methods: A retrospective single-institution study involved 194 records of COVID-19 patients of both genders evaluated according to study objectives, encompassing pertinent data such as age, gender, smoking habits, incidence of anosmia or hyposmia, changes in flavor, initiation and duration of the infection, and alterations in smell and taste. Medications utilized for treatment purposes were either acquired through direct telephone communication with patients or indirectly from patients’ records. Results: A total of 194 patients were included, and the majority of them were women. Patients age had significant differences, with a mean age of 28 years. Infection duration was about 1 week for majority of patients, and the degree of COVID-19 infection was mild. Patients were significantly P ≤ 0.05 had dysgeusia, anosmia, or both of them. Smoking was found to be significantly correlated with dysgeusia. Conclusion: Dysgeusia and anosmia are initial indications of mild COVID-19 infection that resolve on their own during the second phase of the virus’s spread. Young female patients were identified as having a higher propensity to develop dysgeusia, anosmia, or both. Smokers had lower incidence of dysgeusia.